Tribological and thermal properties of a crowned gear pair with high-speed and heavy-load in thermal micro-elastohydrodynamic lubrication. (April 2020) - Xiao, Zeliang; Shi, Xi
The oil film stiffness, temperature rise of oil film, flash temperature and frictional loss ratio of a crowned gear pair with non-Newtonian transient thermal elastohydrodynamic lubrication of rough surfaces in high-speed and heavy-load operating conditions are investigated. The pressure, film thickness, coefficient of friction and temperature rise are calculated along the action line of spur gears to verify the validity of full numerical solution. Subsequently, the effects of high-speed, heavy-load and roughness on those tribological and thermal properties of a crowned gear drive are discussed. The results show that in high-speed, heavy-load and rough surface contact, the crown modification is in favor of stability improvement of gear drive due to smoother curve of oil film stiffness. The temperature rise of the oil film and flash temperature on tooth surface are quite high which are prone to result in gear scuffing. Moreover, small flash temperature and frictional loss ratio occur in the domains near the start of active profile and the tip due to the effect of crown modification.